Hubungan Pengetahuan Ibu Nifas tentang Perawatan Payudara Dengan Kejadian Bendungan ASI di Puskesmas Ngrayun Kecamatan Ngrayun Kabupaten Ponorogo - Sinta Ayu Setiawan; Harnum Rafikasari (Jurnal Delima Harapan, 2017)
Breast care is an act to treat especially during parturition (lactation) to facilitatebreast feeding expenditure. Breast care that is not done properly will cause damlactation, swollen breasts, breast milk can not come out smoothly. At the time of thepreliminary study with observation, the researcher obtained two postpartum mother whosuffered a breast dam until her breasts were injured. The cause is a puerperal motherwho is less aware if the mother does not do breast care properly can cause breast milkdam. This study aims to find out the relationship of knowledge post partum mothers aboutbreast care with the incidence of breast milk dam at Public Health Center Ngrayunsubdristric Ngrayun regency Ponorogo.The type of research is correlational approachwhich maternal knowledge of breast care as an independent variable and the occurrenceof breast milk dam as a dependent variable. The measuring instrument used aquestionnaire. The population of 40 post partum mothers with a sample of 30 post partummothers was taken by purposive sampling technique in January- February 2017 andusing the coefficient contingency statistic test. The result of this study showed thatmothers knowledge about breast care was almost, 14 respondents (46,67%) had lessknowledge cathegory, and 15 respondents (50%) of breast milk dam. Based on thecalculation using the statistical test coefficient contingency with the help of SPSS 18. Forwindows showed that significance level was 0.019 because the significance level 0.019 <0.05 then H0 rejected. This indicated that there was a relationship between maternalknowledge about breast care with the occurrence of breast milk dam at Public HealthCenter Ngrayun subdistrict Ngrayun regency Ponorogo. The researcher suggested topuerperal women play an active role in following each extension so that then can addinformation and improve the ability to perform and treatment of their breast correctlyand understand the importance of how breast care, the ways to keep breast properly soengorgement of breast feeding can be avoided. For healt workers to increase postpartum maternal health services, particularly counselling about breast care, so it canincrease the success of exclusive breast feeding and lowers breast problems.